Modern art in Africa, Asia and Latin America an introduction to global modernisms - O'Brien, Elaine 1945-; Nicodemus, Everlyn; Chiu, Melissa; Ginocchio, Benjamin (Wiley-Blackwell, 2013)
"Shedding fresh light on modern art beyond the West, this text introduces readers to artists, art movements, debates and theoretical positions of the modern era that continue to shape contemporary art worldwide. Area histories of modern art are repositioned and interconnected towards a global art historiography"--Provided by publisher.